In silico analysis of putative polyphenol oxidases in olive using bioinformatics tools - Sevindik, Emre (Bangladesh Journal of Botany, 2019)
Sequence, physicochemical, and three-dimensional structure properties of putative polyphenol oxidase proteins in olive (Olea europaea) using various bioinformatics tools were analyzed. The amino acid length varied from 469 to 582 amino acids. The molecular weights of the proteins (ALG62778.1, AFS28698.1 and AFS28697.1) were 65294.67 Da, 53324.79 Da and 53349.48 Da, and isoelectric points (pI) were 7.58, 7.24 and 6.86, respectively. Instability index values were 40.68, 37.52 and 36.89 while aliphatic index values were 72.08, 73.39 and 73.39 respectively. The GRAVY values were –0.540, –0.580 and –0.578, respectively. The most abundant amino acid was Asp (8.5%) while the least abundant one was Cys (1.4%). The putative phosphorylation sites of the polyphenol oxidase proteins were determined by NetPhos 2.0 and NetPhos 3.1. Based on the phylogenetic analysis, the tree constructed using polyphenol oxidase proteins is composed of two main clades. To predict the three dimensional (3D) structures of these proteins, Py MOL was used. The results of the present study provide insight into fundamental characteristics of putative polyphenol oxidase proteins in Olea europaea.